In vivo and in vitro transcriptomics meta-analyses reveal that BPA may affect TGF-beta signaling regardless of the toxicology system employed. (15th September 2021) - Lu, Yuanping; Yang, Renjun; Yin, Nuoya; Faiola, Francesco
Abstract: Bisphenol A (BPA) is a high-production-volume monomer for the manufacture of a wide variety of polycarbonate plastics and resins. Evidence suggests BPA can induce carcinogenesis, reproductive toxicity, abnormal inflammatory or immune response, and developmental disorders of the brain or nervous system. However, whether BPA affects the very same basic molecular processes in all the in vivo and in vitro systems employed to exert its molecular mechanisms of toxicity remains to be clarified. In this study, we collected multi-source global transcriptomics datasets for BPA-exposed organisms and cells, and evaluated the adverse effects of BPA by using data integration and gene functional enrichment analyses. We found that BPA may affect basic cellular processes, such as cell growth, survival, proliferation, differentiation, and apoptosis, independent of species and specific in vivo or in vitro systems. Mechanistically, BPA could regulate cell-extra cellular matrix interactions via challenging TGF-beta signaling pathways. Furthermore, we compared our in vitro BPA-dependent mouse embryoid body (EB) global differentiation transcriptomics with all the other datasets. We verified the EB-based toxicological system could recapitulate several in vivo and other in vitro findings very efficiently, and in a less time- and resource-consuming fashion. Taken together, this study emphasizes the utility of meta-analyses to understand common molecular mechanisms of toxicity of synthetic chemicals. Graphical abstract: Image 1 Highlights: BPA affects basic cellular processes independent of species and specific in vivo or in vitro assays. BPA may regulate cell-ECM interactions via challenging TGF-beta signaling. EB-based toxicological systems could recapitulate in vivo and other in vitro findings very efficiently.